Electrochemical Cathodic Polarization, a Simplified Method That Can Modified and Increase the Biological Activity of Titanium Surfaces: A Systematic Review. - Jose Carlos Bernedo Alcazar; Mabel Miluska Suca Salas; Marcus Cristian Muniz Conde; Luiz Alexandre Chisini; Flávio Fernando Demarco; Sandra Beatriz Chaves Tarquinio; Neftali Lenin Villarreal Carreño (PLoS ONE)
Background The cathodic polarization seems to be an electrochemical method capable of modifying and coat biomolecules on titanium surfaces, improving the surface activity and promoting better biological responses. Objective The aim of the systematic review is to assess the scientific literature to evaluate the cellular response produced by treatment of titanium surfaces by applying the cathodic polarization technique. Data, sources, and selection The literature search was performed in several databases including PubMed, Web of Science, Scopus, Science Direct, Scielo and EBSCO Host, until June 2016, with no limits used. Eligibility criteria were used and quality assessment was performed following slightly modified ARRIVE and SYRCLE guidelines for cellular studies and animal research. Results Thirteen studies accomplished the inclusion criteria and were considered in the review. The quality of reporting studies in animal models was low and for the in vitro studies it was high. The in vitro and in vivo results reported that the use of cathodic polarization promoted hydride surfaces, effective deposition, and adhesion of the coated biomolecules. In the experimental groups that used the electrochemical method, cellular viability, proliferation, adhesion, differentiation, or bone growth were better or comparable with the control groups. Conclusions The use of the cathodic polarization method to modify titanium surfaces seems to be an interesting method that could produce active layers and consequently enhance cellular response, in vitro and in vivo animal model studies.